Estimation of the convergence rate of two-dimensional random index vectors maxima - Dindienė, Lina; Jokimaitis, Arvydas (Lietuvos matematikos rinkinys, 2011)
Nonlinearly normalized maxima of independent and identically distributed random vectors are pre-sented in this work. We’ve obtained nonuniform estimate of convergence in transfer theorem in case when normalization is nonlinear.